Foxm1 is a critical driver of TGF‐β‐induced EndMT in endothelial cells through Smad2/3 and binds to the Snail promoter. Issue 6 (30th October 2018) - Song, Shuai; Zhang, Rui; Cao, Wei; Fang, Guojian; Yu, Yi; Wan, Yi; Wang, Chuanhui; Li, Yigang; Wang, Qunshan
Abstract: Endothelial‐to‐mesenchymal transition (EndMT) was first reported in heart development. Recent studies have shown that EndMT also occurs in the progression of cardiac fibrosis. Herein, we demonstrated a critical role of the Forkhead Box M1 (Foxm1) transcription factor in transforming growth factor beta (TGF‐β)‐induced EndMT in endothelial cells (ECs) and a possible underlying molecular mechanism. Foxm1 was induced in ECs following TGF‐β stimulation. Using both pharmacological and molecular approaches to inhibit Foxm1 function can attenuate the TGF‐β‐induced EndMT and cell migration. In contrast, lentivirus‐mediated overexpression of Foxm1 allowed EndMT to proceed despite the absence of TGF‐β in ECs. Moreover, we found that the activation of the Smad2/3 signaling pathway and EndMT‐related transcription factors played important roles in the pathogenesis of Foxm1‐mediated EndMT. Further analysis revealed that Foxm1 bound to and increased the promoter activity of the Snail gene encoding a critical transcriptional regulator of EndMT. In conclusion, our results identify FOXM1 as a driver of TGF‐β‐induced EndMT and underscore the therapeutic potential of targeting FOXM1 for cardiac fibrosis. Abstract : We found that the activation of the Smad2/3 signaling pathway and endothelial‐to‐mesenchymal transition (EndMT)‐related transcription factors played important roles in the pathogenesis of Forkhead Box M1 (Foxm1)‐mediated EndMT. Our results identify FOXM1 as a driver of TGF‐β‐induced EndMT and underscore the therapeutic potential of targeting FOXM1 for cardiac fibrosis.